The effect of breast support on the kinematics of the breast during the running gait cycle - Scurr, J. C.; White, J. L.; Hedger, W. (Journal of Sports Sciences, 2010)
Although breast pain has been related to vertical breast displacement and velocity, the influence of breast support on multi-planar breast kinematics and breast comfort has yet to be ascertained. The aims of this study were to investigate multi-planar breast displacement, velocity, and acceleration with and without breast support during running and to establish the correlation with breast comfort. Fifteen females ran at 2.8 m/s in no bra, an everyday bra, and a sports bra. Three-dimensional coordinates of breast and body markers were tracked during ten gait cycles and following each trial the participants rated their breast comfort. Relative breast displacement was calculated and derived for velocity and acceleration. Vertical breast displacement, velocity, and acceleration peaked at, before, and after mid-stance, respectively. The patterns of displacement and velocity trajectories were unaffected by increasing breast support, though the magnitudes were significantly reduced. The magnitude and trajectory of breast acceleration was unaffected by increasing breast support and showed no correlation with comfort. Breast velocity displayed the strongest relationship to comfort (r = 0.61). Considerable mediolateral and anteroposterior breast kinematics were identified, suggesting that future studies and bra design may benefit from three-dimensional analysis. In conclusion, improvements in breast support may be defined by reductions in breast velocity and displacement.